Palaeomagnetism and Rb-Sr ages of the Ratagan and Comrie intrusions - Turnell, H. B. (Geophysical Journal International, 1985)
Study of the palaeomagnetism of two complexes from the Newer Granite Suite in Scotland, at Ratagan (NW Highlands) and Comrie (central Highlands), reveals the variable nature of the natural remanence encountered in granodioritic intrusions and the surrounding metamorphic country rock. Forty-eight specimens from Ratagan, dated at 415 ± 5 Ma, gave a mean direction: D = 8°, I = −32°, and a palaeomagnetic south pole: 15°S, 346°E (δ p = 5°, δ m = 9°). Twenty-eight specimens from Comrie, dated at 408±5 Ma, gave a mean direction: D = 75°, I = −30°, and a palaeomagnetic south pole: 6°S, 287°E (δ p = 4°, δ m = 7°). These results have been compared with the established apparent polar wander path (APWP) for Britain. The Ratagan pole improves the reliability of the APWP but doubt remains as to whether the primary magnetization from Comrie represents a true late Silurian direction or whether it has been affected by post-cooling rotation, possibly associated with the nearby Highland Boundary Fault.